Perinatal paracetamol exposure in mice does not affect the development of allergic airways disease in early life. Issue 6 (3rd April 2015) - Lee, Debbie C P; Walker, Simone A; Byrne, Adam J; Gregory, Lisa G; Buckley, James; Bush, Andrew; Shaheen, Seif O; Saglani, Sejal; Lloyd, Clare M
Abstract : Background: Current data concerning maternal paracetamol intake during pregnancy, or intake during infancy and risk of wheezing or asthma in childhood is inconclusive based on epidemiological studies. We have investigated whether there is a causal link between maternal paracetamol intake during pregnancy and lactation and the development of house dust mite (HDM) induced allergic airways disease (AAD) in offspring using a neonatal mouse model. Methods: Pregnant mice were administered paracetamol or saline by oral gavage from the day of mating throughout pregnancy and/or lactation. Subsequently, their pups were exposed to intranasal HDM or saline from day 3 of life for up to 6 weeks. Assessments of airway hyper-responsiveness, inflammation and remodelling were made at weaning (3 weeks) and 6 weeks of age. Results: Maternal paracetamol exposure either during pregnancy and/or lactation did not affect development of AAD in offspring at weaning or at 6 weeks. There were no effects of maternal paracetamol at any time point on airway remodelling or IgE levels. Conclusions: Maternal paracetamol did not enhance HDM induced AAD in offspring. Our mechanistic data do not support the hypothesis that prenatal paracetamol exposure increases the risk of childhood asthma.